Pedagogická diagnostika a pedagogické diagnostikování Učební materiál - Kratochvílová, Jana (Masaryk University Press, 2021)
Title in English: Educational assessment and diagnostic assessment: Textbook The textbook introduces students to diagnostic assessment and the theory of educational assessment. Students get acquainted with the basic methods and tools of educational assessment, learn about the process of diagnostic activities and the importance of cooperation with experts during diagnostic activities in practice. The study text is supplemented by practical examples and links to further resources that can help students understand teachers' diagnostic work.